2008
DOI: 10.1136/bjo.2007.133496
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localisation of intravitreally injected bevacizumab in the anterior chamber angle, iris and ciliary body of the primate eye

Abstract: Bevacizumab penetrates quickly into the iris, anterior chamber angle and ciliary body after intravitreal injection in the primate eye and accumulates particularly in blood-vessel walls. The highest concentration of bevacizumab in these tissues is present on day 1-4, the iris and anterior chamber angle being penetrated slightly earlier than the ciliary body. Our findings support the clinically observed rapid effect in the treatment of iris neovascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…In an animal study, bevacizumab penetrated quickly into the iris, anterior chamber angle and ciliary body after IVB. This finding supports the clinically observed rapid effect of bevacizumab in the treatment of iris neovascularization [64]. This injection may provide us with sufficient time to treat these patients with retinal photocoagulation.…”
Section: Neovascular Glaucomasupporting
confidence: 85%
“…In an animal study, bevacizumab penetrated quickly into the iris, anterior chamber angle and ciliary body after IVB. This finding supports the clinically observed rapid effect of bevacizumab in the treatment of iris neovascularization [64]. This injection may provide us with sufficient time to treat these patients with retinal photocoagulation.…”
Section: Neovascular Glaucomasupporting
confidence: 85%
“…19,29,33 In animal studies, the immunoreactivity of bevacizumab was detected in blood vessel walls of the iris, anterior chamber angle, ciliary body, choroid, and the inner layers of the retina, especially in the ganglion cell layer and inner nuclear layer. 19,29,33 The VEGF immunoreactivity was found to be nondetectable for the next 14 days after bevacizumab injection.…”
Section: Discussionmentioning
confidence: 98%
“…19,29,33 In animal studies, the immunoreactivity of bevacizumab was detected in blood vessel walls of the iris, anterior chamber angle, ciliary body, choroid, and the inner layers of the retina, especially in the ganglion cell layer and inner nuclear layer. 19,29,33 The VEGF immunoreactivity was found to be nondetectable for the next 14 days after bevacizumab injection. 29 In the studies reported by Heiduschka et al 19 and Shahar et al, 34 immunoreactivity of bevacizumab could not be detected 25 days and 30 days after intravitreal injection, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…This may allow intravitreal BV to diffuse toward and reach the VR junction sooner, and it may also enable the molecule to leave the intraocular cavity via alternative exit routes. Intravitreal BV has been shown to penetrate into the iris, ciliary body, and anterior chamber angle shortly after injection, and its distribution in the anterior chamber angle is time-dependent 30. Two exit pathways have been described to explain the distribution and the decline in ranibizumab levels in the vitreous cavity and aqueous humor 31.…”
Section: Discussionmentioning
confidence: 99%